Foreplay - Jordan, Sophie (Jordan, Sophie. Ivy chronicles., 2013)
Pepper has been hopelessly in love with her best friend's brother, Hunter, for, like, ever. He's the key to everything she's always craved: security, stability, family. But she needs Hunter to notice her as more than just a friend. Even though she's kissed exactly one guy, she has the perfect plan to go from novice to rock star in the bedroom: take a few pointers from someone who knows what he's doing. Her college roommates have the perfect teacher in mind. But bartender Reece is nothing like the player Pepper expects. Yes, he's beyond gorgeous, but he's also dangerous and deep with a troubled past. Soon what started as a lesson in attraction is turning both their worlds upside down, and showing them just what can happen when you go past foreplay and get to what's real.